Impact of Human Resources Practices on Service Quality: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Out of the 800distributed questionnaires, we could collect 615 questionnaires. Only 530 ofthe returned questionnaires by whatever methods were found suitable for finalanalysis and without discrepancies. Remaining 85 questionnaires were rejectedas they were incomplete in one respect or the other. The detailed descriptionof the sample can be seen through Table 3.1. Out of the sample of 530respondents, 312 (150 government sector and 162 private/multinational)respondents were from banks and 218 (123 government sector and 95private/multinational) were from insurance companies. All respondent employees/managers were of Indian origin.